Novel setting-less pilot protection for MMC HVDC grids - Chenhao Zhang; Bowen Chen; Anyi Zhao; Guobing Song (International Journal of Electrical Power & Energy Systems)
The determination of a suitable threshold is challenging for most of existing pilot protections of MMC HVDC systems. There are two kinds of setting-less pilot protection among the existing research: current polarity-based and inductor voltage-based pilot directional protections. However, these methods have inherent flaws in certain fault situations accompanied with sharp fluctuations. To address these issues, a novel setting-less pilot protection is proposed based on the idea of pattern recognition. Firstly, the relationship between one-mode fault component voltage and current is analyzed. It can be concluded that Δu ∝ dΔi/dt when forward fault occurs, and Δu ∝ Δi when backward fault occurs. Therefore, the correlation coefficients ρR(Δu, Δi) and ρL(Δu, dΔi/dt) are defined. |ρR| < |ρL| indicates forward faults, and |ρR| > |ρL| indicates backward faults. The proposed protection can recognize faults within less than 1 ms, and have higher tolerability against transition resistance. It avoids complex threshold setting, and can be applied to various system states and fault conditions. It performs well in those situations where existing setting-less protections may fail. Both simulations and physical experiments have validated the effectiveness of the proposed protection, and have shown that the proposed method is simple for application and of high reliability.